Definitions, diagnostic criteria and terminality assessment of cancer and noncancer chronic diseases - Amado, José (2020)
Global demographic changes have generated new challenges in the health system. Treating increasingly older patients with more complex health problems has significantly raised and exceeded our response capacity, and Peru is not indifferent to this situation. These patients need more and more care, and late-stage chronic diseases require an approach change: from aggressive healing treatments to palliative ones which improve quality of life and are associated with an important social content. Late-stage diseases occur in the final stage of life, where irreversible damage; multiple somatic, psychological and spiritual symptoms; as well as great impact in the patients and their families take place. Late-stage cancer diseases have been studied on a relatively frequent basis; however, non-cancer diseases occur more often and result in better survival rates. This review article aims at gathering the operational definitions of this condition, describing the specific diagnostic criteria of terminality, and summarizing the instruments to identify the need of palliative care and the prognostic scales published in the scientific literature.